UJI EFEK ANTIINFLAMASI EKSTRAK ETANOL HERBA KROKOT (Portulaca oleracea L.) TERHADAP TIKUS PUTIH (Rattus norvegicus) JANTAN - SALIM, MUH.AGUS; Azizah, Rizqi Nur; Putra, Bayu (SAINS INDONESIANA, 2024)
Portulaca oleracea L. is assumed to contain flavonoids as anti-inflammatory agent bya inhibiting the cyclooxygenase enzyme. The research aimed determine the anti-inflammatory effect and affective dose of ethanol extract of Portulaca oleracea L. on rats. The research used 20 rats divided into 5 groups. Each group consisted of 4 rats. Group I (negative control) was given Na.CMC 1%, group II (comparator) was given diclofenac sodium, groups III, IV and V (treatment group) were given ethanol extract at 100 mg/kgBW. 200 mg/kgBW and 400 mg/kgBW. The method used was Rat Hind Paw Edema by measuring the volume of rat feet induced with 0,1% w/v carrageen A of 0,1 ml on the soles by intraplantar. The analysis showed e decrease in edema volume statistically done using one way ANOVA proceeded with LSD test. The results of the research indicated that the ethanol extract of Portulaca oleracea at the dose 400 mg/kgBW had anti-inflammatory effect.